A comparative evaluation of effect of intravenous premedication with ondansetron versus granisetron on hemodynamics and sensory-motor blockade produced by intrathecal hyperbaric 0.5% bupivacaine - Kumar, Abhishake; Inayat, Umar; Rastogi, Bhawana; Gupta, Kumkum; Jain, Manish; Tayal, Arshiya (International Journal of Research in Medical Sciences, 2019)
Background: Bezold Jarisch reflex is important cause of hypotension and bradycardia which occur after spinal anaesthesia. This reflex is elicited by stimulation of peripheral serotonin receptors 5- hydroxytryptamine (5- HT3 type). These receptors have antinociceptive effect, which is confirmed by many studies.The two most commonly used 5HT3 antagonist are ondansetron and granisetrone. Very few comparative studies of the two drugs on the effect after spinal anaesthesia are available. Methods: Ninety adulted patients of either sex aged 18-58 years scheduled for elective infraumbilical surgeries were randomly allocated in three groups to receive intravenous ondansetron 4mg, granisetrone 2mg or normal saline in equal volume 5mins before spinal anesthesia. Hemodynamic changes and time to sensory motor onset and regression were evaluated. Results: There was statistically significant difference in fall of systolic diastolic and mean blood pressure among the three groups. Time to two segment regression of sensory block and time to regression to S1 was faster in ondansentron (76.6±17.2mins, 176±22mins) and granisetrone group (69±17.3mins, 165±19.2mins) in comparision to control group(77.4±24.3mins, 178±21mins) which was statistically significant also p value-0.019, 0.0001 respectively. Conclusions: The prophylactic therapy with 4mg i.v. ondansetron, given five minutes before spinal anaesthesia appears to be significantly most effective and safe for attenuating haemodynamic response after spinal anaesthesia without affecting the duration of sensory block in patients undergoing infraumbilical surgeries.